Engineered Wetland in University Teknologi Petronas Core Park - Poh, Haw Seng (Universiti Teknologi Petronas, 2006)
The objective of the project is to design and implement a new wetland which can provide stable flood mitigation system and balance ecological system. The new design is based on the combination of wetland, orifices and spillway with the purpose to improve the existing UTP Core Park wetland. UTP wetland was initially designed for landscaping purpose. Improvement of the wetland is proposed for the sustainability of the wetland with suitable flora and fauna to be located in the wetland. Without any experience on designing a wetland system, the hydraulic calculations, biological system, and laboratory tests, varied tasks are very challenging to complete. Information from internet and book and the advice from lecturers are the important factors that lead to the completion of this project. The scope of study of this project covers a wide range of engineering and biological scopes. The engineering scope included in the study covers the existing wetland design capacity, engineering landscape design, calculation of the orifices sizing, calculations of pipe culvert, and calculation of spillway sizing. The study also include ecological scope namely study on flora and fauna and water quality. With this project; student can understand about the concept and application of wetland design. In the calculation part, all the important parameters will be discussed in more detail for better understanding of the design, considerations. A new design will proposed and the discussion is included in this report to meet the objective of the project At the end of the report, recommendations were suggested for further improvement about the new design. The suggestions were made for future improvement in the design. The whole finding of this project is concluded at the last section as the conclusion of this thesis.